Penggunaan Jobsheet Interaktif dalam Praktikum Analisis Rangkaian Listrik dan Elektronika - Nopitasari, Fitri; Purnama, Wawan (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
The rapid growth of science and technology in the era of globalization is resulting in changes to the circumstances in all areas. Interactive Jobsheet utilization in the lab performed as learning innovation efforts to improve students' level of proficiency in performing lab work correctly, different learning styles, accompanied jobsheet that uses a computer in a way that will easily evoke the spirit of the students in learning, improving students' attention to the subject material and to improve the effectiveness in implementing practical. Research using quantitative descriptive method with the subject is the first class of Aircfraft Eelectronic at Vocational High School 12 Bandung, with a population sample of 32 students. Data was collected through questionnaires, multiple-choice objective test and lab test. Data processing is performed by calculating the linearity test and the significance of regression, correlation coefficients and coefficients of determination with the help of Microsoft Excel 2007. The results of the calculations provide an overview of how the questionnaire responses of students in the interactive jobsheet utilization, while the objective test and lab tests showed the level of mastery and student learning outcomes. The results of the calculation of the correlation coefficient and the coefficient of determination, the response of the students in the Interactive Jobsheet utilization has a positive influence on students' level of proficiency in performing lab. with standard medium / fairly